EFEKTIVITAS PENANGANAN EMISI GAS BUANG PADA KENDARAAN DI JAKARTA (DITINJAU DARI PERATURAN GUBERNUR DKI JAKARTA NOMOR 66 TAHUN 2020 TENTANG UJI EMISI GAS BUANG KENDARAAN BERMOTOR) - Ovaldo Noor Hakim; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
Air has the crucial role to play to all living beings, especially humanity. As ages progress swiftly, cities are racing in terms of the rapid development of its industrial centre. There are no doubts when a city grows more sophisticated, transportation systems are needed more than ever for the intention of facilitating and accelerating citizen’s mobility. As a result of gas emissions from transportation, air has become more polluted from all the uses of transportations. The fact is most citizens lack the will to use public transportation and are more interested in choosing to use their personal transportations. Through the method of  literature, it’s crystal clear that there are a couple of cases that we need to observe, that include 1. The use of a transportation’s appropriateness 2. Transportation’s age 3. The needs of testing gas emission from transportation per period of time 4. Increasing the sum of city forest for the intent of absorbing gas emissions from vehicles 5. Implementing permissions restrictions of the private transportation users 6. Socialize the use of public transportation.